INTERNAL FACTORS AND COMPANYS VALUE - Irma Christiana; Raihana Daulay (Proceeding International Seminar of Islamic Studies, 2022)
This purpose of this study was to determine the effect of the companys fundamental factors represented by return on equity and debt to equity ratio on the price to book value through earning per share as an intervening variabel on the Jakarta Islamic index. This type of research is quantitative associative research. The research population was 30 companies, the sampling method used purposive sampling method so that 7 companies were selected while the data sample was 35 data. The data used are secondary data and time series. Data analysis using regression and path analysis. The findings of this study are that return on equity have no effect on earning per share, but debt to equity ratio has an effect on earning per share. The next finding is that return on equity has an effect on price to book value, whereas debt to equity ratio and earning per share have no effect on price to book value. Furthermore, earning per share can mediate the effect of return on equity on price to book value, but cannot mediate the effect of debt to equity ratio on price to book value.Keywords: return on equity, debt to equity ratio, earning per share, price to book value